2021
DOI: 10.3389/fmolb.2021.754443
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Natural Killer Cell Therapies in Glioblastoma Multiforme Using Supramolecular Cationic Inhibitors of Heat Shock Protein 90

Abstract: Allogeneic natural killer (aNK) cell adoptive therapy has the potential to dramatically impact clinical outcomes of glioblastoma multiforme (GBM). However, in order to exert therapeutic activity, NK cells require tumor expression of ligands for activating receptors, such as MHC Class I peptide A/B (MICA/B) and ULBPs. Here, we describe the use of a blood–brain barrier (BBB) permissive supramolecular cationic drug vehicle comprising an inhibitor of the chaperone heat shock protein 90 (Hsp90), which sustains a cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These results are the opposite of the study that employed a bioinformatics approach querying open repositories and pooling data from several clinical studies with over 1500 samples [ 98 ]. The study found mRNA expression of Hsp90 to be the highest in glioblastoma when compared to other tumor types, such as astrocytoma, and oligodendrogliomas, and the chaperon expression has the inverse correlation with disease-free survival ( Figure 8 ) [ 98 ]. The same association with survival was found by Sun et al, where HSP90B1 increased expression led to a shorter survival time [ 72 ].…”
Section: Expression Of Hsps In Brain Tumorsmentioning
confidence: 66%
See 1 more Smart Citation
“…These results are the opposite of the study that employed a bioinformatics approach querying open repositories and pooling data from several clinical studies with over 1500 samples [ 98 ]. The study found mRNA expression of Hsp90 to be the highest in glioblastoma when compared to other tumor types, such as astrocytoma, and oligodendrogliomas, and the chaperon expression has the inverse correlation with disease-free survival ( Figure 8 ) [ 98 ]. The same association with survival was found by Sun et al, where HSP90B1 increased expression led to a shorter survival time [ 72 ].…”
Section: Expression Of Hsps In Brain Tumorsmentioning
confidence: 66%
“…** p < 0.01, **** p < 0.0001 analyzed by ordinary one-way ANOVA with Tukey’s multiple-comparison test. ( B ) Copy number alteration (CNA) evaluated across seven clinical studies (cBioPortal) [ 98 ].…”
Section: Figurementioning
confidence: 99%
“…Knowing that NK cytotoxicity is partially dependent on NKG2D for instance, could steer the development of combination therapies preventing shedding of its ligand MICA/B from tumor cells, 46 or boosting ligand expression using an inhibitor of heat shock protein 90. 47 Moreover, we observed that NKp46 seems to play an important role in NK activation. Therefore, combination with NK cell engagers that allow simultaneous targeting of NKp46 on NK cells and a target antigen on the tumor could be an interesting approach.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, we focused on molecular chaperones. These are the chief members of the CS and are known to play key roles in carcinogenesis, both anti-and pro-tumoral roles [11,14,29,[35][36][37][38][39]. They are also promising candidates as biomarkers for differential diagnosis, prognostication, and patient follow up.…”
Section: Discussionmentioning
confidence: 99%